2022
DOI: 10.1130/g49167.1
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal evolution of the Christiana-Santorini-Kolumbo volcanic field, Aegean Sea

Abstract: The Christiana-Santorini-Kolumbo volcanic field (CSKVF) in the Aegean Sea is one of the most active volcano-tectonic lineaments in Europe. Santorini has been an iconic site in volcanology and archaeology since the 19th century, and the onshore volcanic products of Santorini are one of the best-studied volcanic sequences worldwide. However, little is known about the chronology of volcanic activity of the adjacent submarine Kolumbo volcano, and even less is known about the Christiana volcanic island. In this stu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
109
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(109 citation statements)
references
References 21 publications
(31 reference statements)
0
109
0
Order By: Relevance
“…The eruption recurrence interval at Kolumbo is unknown, as only the last of five recognised eruptive phases has been dated with confidence (Nomikou et al, 2016). A sequence stratigraphic analysis indicates that all these phases occurred during the last 1.2 Ma, suggesting an average recurrence interval of ~240 ka (Preine et al, 2021). A lower bound of 10 ka was proposed based on seismic reflection data and the tectonic history of the region (Hübscher et al, 2015).…”
Section: Long-term Evolution and Present Statementioning
confidence: 99%
“…The eruption recurrence interval at Kolumbo is unknown, as only the last of five recognised eruptive phases has been dated with confidence (Nomikou et al, 2016). A sequence stratigraphic analysis indicates that all these phases occurred during the last 1.2 Ma, suggesting an average recurrence interval of ~240 ka (Preine et al, 2021). A lower bound of 10 ka was proposed based on seismic reflection data and the tectonic history of the region (Hübscher et al, 2015).…”
Section: Long-term Evolution and Present Statementioning
confidence: 99%
“…Hübscher et al, 2015;Nomikou et al, 2014). Reflection seismic profiles crossing the Kolumbo edifice revealed five circular, stacked, cone-shaped, units, with the uppermost one deposited during the 1650 AD eruption (C. Hübscher et al, 2015;Preine et al, 2021). Precise dating is only available for the latest eruption of Kolumbo.…”
Section: Geological Setting Of Kolumbo and Eruption Historymentioning
confidence: 99%
“…Precise dating is only available for the latest eruption of Kolumbo. However, a recently established regional stratigraphic framework of the entire CSKVF region estimates that the deposits of older eruptions have approximate ages of 0.35 Ma, 0.45 Ma, 0.9 Ma and older than 1.0 Ma (Preine et al, 2021).…”
Section: Geological Setting Of Kolumbo and Eruption Historymentioning
confidence: 99%
“…Examples from the Hellenic Volcanic Arc in the densely populated Aegean Sea are sparse despite the known occurrence of large‐scale volcanic centres and enhanced seismicity, which make this arc one of the major risk factors for the eastern Mediterranean (Sørensen et al, 2012). Preine et al (2022) reported a large mass‐transport deposit within the Christiana‐Santorini‐Kolumbo volcanic field (CSKVF) in the central Aegean Sea. Chrono‐stratigraphic relationships indicate that the deposit was emplaced during the early evolution of Santorini, approximately 0.7 Myrs ago (Preine et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Preine et al (2022) reported a large mass‐transport deposit within the Christiana‐Santorini‐Kolumbo volcanic field (CSKVF) in the central Aegean Sea. Chrono‐stratigraphic relationships indicate that the deposit was emplaced during the early evolution of Santorini, approximately 0.7 Myrs ago (Preine et al, 2022). However, the distribution, volume, trigger mechanisms and emplacement dynamics of the deposit have not been investigated so far.…”
Section: Introductionmentioning
confidence: 99%